UPAYA KOREA TOURISM ORGANIZATION (KTO) DALAM MEMPROMOSIKAN PARIWISATA KOREA DI INDONESIA - Rianti "; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain, the effort of the Korea Tourism Organization (KTO) to promote Korean tourism in Indonesia. Korea and Indonesia have a good cooperative relationship. The Korean government established KTO in Indonesia, because Indonesia has the third largest number of hallyu fans in the world.This research uses the Perspective of Globalization, the level of analysis of nation states, and Theory of International Tourism. The method used is a qualitative research method. This analysis is based on data obtained from literature studies, interviews with an informant over the phone, and from KTO official site.The results of the research in this paper are that KTO has programs to promote Korean tourism in Indonesia from 2016 to 2018. These programs are top idol as brand ambassador of tourism, KTO cooperates with the private sectors, halal tourism and muslim friendly, Korea Festival as cultural festival, and a special microsite for Indonesian tourists.Keyword : Globalization, International Tourism, Korean Tourism, Korea Tourism Organization, Indonesian Tourists.